Examining the effectiveness of a GeoGebra-assisted open-ended approach on students’ mathematical creative thinking ability - Andini Dwi Rachmawati; Dadang Juandi; Darhim Darhim (Universitas Hamzanwadi, 2023)
Researchers use open-ended as a learning method to help students improve their math skills. Each open investigation of mathematical knowledge produces mixed results for components of mathematical ability, each school level, and the content taught. There are more and more studies on open-ended questions nowadays. This study tested the effectiveness of the open-ended approach assisted by GeoGebra on students' mathematical creative thinking abilities. The use of meta-analysis techniques is to analyze the effect (effect size) of a preliminary study. The instruments used were coding protocol sheets and coding sheets/Comprehensive Meta-Analysis (CMA) programs to analyze data. The resulting findings are that there are differences in the research method with the most significant effect size in the quasi-experimental research method, the research year with the most significant effect size in the 2012-2022 research year, indexing journals with the most significant effect size on web indexing scientific journals; the type of publication that has the most critical influence on the kind of thesis publication. Furthermore, the GeoGebra-assisted open-ended approach to creative thinking ability has no significant effect when viewed from the research characteristics of the sample size and level of education.